Mechanism-based design of agents that selectively target drug-resistant glioma - Lin, Kingson; Gueble, Susan E.; Sundaram, Ranjini K.; Huseman, Eric D.; Bindra, Ranjit S.; Herzon, Seth B. (Science (American Association for the Advancement of Science), 2022)
Approximately half of glioblastoma and more than two-thirds of grade II and III glioma tumors lack the DNA repair protein O 6 -methylguanine methyl transferase (MGMT). MGMT-deficient tumors respond initially to the DNA methylation agent temozolomide (TMZ) but frequently acquire resistance through loss of the mismatch repair (MMR) pathway. We report the development of agents that overcome this resistance mechanism by inducing MMR-independent cell killing selectively in MGMT-silenced tumors. These agents deposit a dynamic DNA lesion that can be reversed by MGMT but slowly evolves into an interstrand cross-link in MGMT-deficient settings, resulting in MMR-independent cell death with low toxicity in vitro and in vivo. This discovery may lead to new treatments for gliomas and may represent a new paradigm for designing chemotherapeutics that exploit specific DNA repair defects. A glioma is a tumor of the glial cells found in the brain and spinal cord. Glioblastoma multiforme (GBM) is the most common type of glioma, and is a highly aggressive brain tumor in dire need of new treatment strategies. GBM is frequently treated with the chemotherapy drug temozolomide (TMZ), but resistance develops in more than half of patients. Using a medical chemistry approach, Lin et al . designed TMZ analogs to overcome drug resistance in GBM (see the Perspective by Reddel and Aref). These agents generate a primary DNA lesion that can be repaired by healthy cells with intact DNA repair mechanisms. However, cancer cells that lack DNA-repair machinery are not able to repair the damage and slowly evolve to harbor more toxic secondary lesions that cause selective tumor cell killing. —PNK Bifunctional agents exploit tumor-associated DNA repair defects to selectively generate cytotoxic DNA interstrand cross-links in tumor cells.